On Water (Volume 1) - Arthus-Bertrand, Yann (European Investment Bank, 2021)
When taking a drink is as easy as turning a tap, it is easy to forget that our water supply is fragile and that hundreds of millions of people do not have clean drinking water or proper sanitation.The human impact on our land, the oceans and the climate is endangering our future. In a world accustomed to instant gratification and immediate consumption, we need more than ever long-term thinking and action to safeguard our natural resources. Award-winning French photographer and environmentalist Yann Arthus-Bertrand reminds us that water is precious and that we need a new approach to protect the planet’s vital elements. This is the first essay in the Big Ideas series created by the European Investment Bank. The EIB has invited international thought leaders to write about the most important issues of the day. These essays are a reminder that we need new thinking to protect the environment, promote equality and improve people’s lives around the globe.